If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2y + 1) = 2(12y) Reorder the terms: 4(1 + 2y) = 2(12y) (1 * 4 + 2y * 4) = 2(12y) (4 + 8y) = 2(12y) Remove parenthesis around (12y) 4 + 8y = 2 * 12y Multiply 2 * 12 4 + 8y = 24y Solving 4 + 8y = 24y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-24y' to each side of the equation. 4 + 8y + -24y = 24y + -24y Combine like terms: 8y + -24y = -16y 4 + -16y = 24y + -24y Combine like terms: 24y + -24y = 0 4 + -16y = 0 Add '-4' to each side of the equation. 4 + -4 + -16y = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -16y = 0 + -4 -16y = 0 + -4 Combine like terms: 0 + -4 = -4 -16y = -4 Divide each side by '-16'. y = 0.25 Simplifying y = 0.25
| 3*(x-2)-(x-5)=13 | | 0.75(h+4)=13.5 | | 11X+3=3X+35 | | x^2-9x+6=6 | | H(x)=4x^2+2x-5 | | 7+8=16 | | 2x^3+9x^2-7x+1=0 | | -1=0(3)+b | | 75-3x=5-10x | | (4y^2+9)(16y^2+.25)=0 | | 3x=-y+140 | | 2x^2+x+y+2y^2+2x+5-2x^2+y^2-7= | | 5*(2x-1)+(3x-32)=67 | | 2x+11=-17-5x | | 2=.66(-3)+b | | 5a-5whena=4 | | 2t^2+13t=7 | | 0.75(h+4)=7 | | 12x+2=10+4x | | 3=3(-2)+b | | 3x+5x-4=6x+5 | | 3(.75m+10)+2.50m-15=2(1.75m+12.50)-.75+4 | | 4=-0.5(-2)+b | | 3(3x-85)=4x | | 6+42x=21x+24 | | 11-22x= | | 3*(2x-1)+(3x-32)=67 | | -x^2-49=0 | | 100=x-15 | | 8n+30=5n+4 | | 4(4x+8)=3x | | 5x+2x-3=(-3)x+10 |